The Influence of Organizational Commitment on Omani Public Employees' Work Performance - Salim Musabah Bakhit Al Zefeiti; Noor Azmi Mohamad (International Review of Management and Marketing, 2017)
The purpose of this paper is to investigate the influence of organizational commitment on work performance in the context of Omani governmental organizations. Organizational commitment through its affective commitment, normative commitment, continuance commitment, motivates employees to work for the good of the organization. There are various studies that discuss organizational commitment, and work performance, yet it is hardly to see the research done on interrelationship between organizational commitment subscales and employees' work performance specifically in Omani context. Thus, the paper is an attempt to fill this gap in the literature. Organizational Commitment Questionnaire (OCQ) was used to measure organizational commitment. Contextual and task performance were used to measure work performance. Quantitative survey method was applied and a sample of 335 middle-level managers of Omani public civil service organizations was selected to answer the instrument. Analysis of Moment Structures (AMOS) was utilized to analyse the collected data and test the research questions, and hypotheses.  The techniques of data analysis comprised a Confirmatory Factor Analysis (CFA), and a Structural Equation Modeling (SEM) analysis. The empirical results indicate that all organizational commitment subscales (affective, normative, and continuance) have a significant impact on work performance dimensions, contextual and task performance.